The challenges of modelling microphysics: ambipolar diffusion, chemistry, and cosmic rays in MHD shocks. Issue 1 (5th January 2019) - Grassi, T; Padovani, M; Ramsey, J P; Galli, D; Vaytet, N; Ercolano, B; Haugbølle, T
ABSTRACT: From molecular clouds to protoplanetary discs, non-ideal magnetic effects are important in many astrophysical environments. Indeed, in star and disc formation processes, it has become clear that these effects are critical to the evolution of the system. The efficacy of non-ideal effects is, however, determined by the complex interplay between magnetic fields, ionizing radiation, cosmic rays, microphysics, and chemistry. In order to understand these key microphysical parameters, we present a one-dimensional non-ideal magnetohydrodynamics code and apply it to a model of a time-dependent, oblique, magnetic shock wave. By varying the microphysical ingredients of the model, we find that cosmic rays and dust play a major role, and that, despite the uncertainties, the inclusion of microphysics is essential to obtain a realistic outcome in magnetic astrophysical simulations.